2020
DOI: 10.1259/bjr.20190866
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax rates in CT-Guided lung biopsies: a comprehensive systematic review and meta-analysis of risk factors

Abstract: Objective: This systematic review and meta-analysis investigated risk factors for pneumothorax following CT-guided percutaneous transthoracic lung biopsy. Methods: A systematic search of nine literature databases between inception to September 2019 for eligible studies was performed. Results: 36 articles were included with 23,104 patients. The overall pooled incidence for pneumothorax was 25.9% and chest drain insertion was 6.9%. Pneumothorax risk was significantly reduced in the lateral decubitus position whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 47 publications
2
78
3
2
Order By: Relevance
“…In the present study, pneumothorax developed in 30% of CTLB procedures, comparable to previous studies [9,20]. Of all cases of pneumothorax, 16.1% was delayed occurrence.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, pneumothorax developed in 30% of CTLB procedures, comparable to previous studies [9,20]. Of all cases of pneumothorax, 16.1% was delayed occurrence.…”
Section: Discussionsupporting
confidence: 91%
“…Among variables contributing to the risk of pneumothorax, factors other than small lesion size remain controversial [ 9 , 19 , 21 24 ]. Our study showed small lesion size as the only consistent factor related to both immediate and delayed pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…209 Other studies including a meta-analysis of 36 studies with 23,104 patients identified several risk factors for pneumothorax: lateral decubitus position where the biopsied lung was nondependent compared to supine (OR: 2.28) or prone position (OR: 3.20), larger caliber guide/needles ( 18 G vs. >18 G: OR 1.55), fissure crossed (OR: 3.75), bulla crossed (OR: 6.13), multiple pleural punctures (>1 vs. 1: OR: 2.43), multiple noncoaxial tissue sample (>1 vs. 1: OR 1.99), emphysematous lungs (OR: 3.33), smaller lesions (<4 cm vs. 4 cm: OR: 2.09), lesions without pleural contact (OR: 1.73), deeper lesions (!3 cm vs. <3 cm: OR: 2.38) and operator experience. [209][210][211] Severe COPD, previous pneumonectomy, use of home oxygen and moderate to severe pulmonary hypertension are relative contraindications to PTNB. 207 Preoperative PTNB to confirm malignancy in patients with suspicious moderate-risk to high-risk lung nodules may lead to decreased costs and a lower probability of resecting nonmalignant lesions.…”
Section: Section 6 Diagnostic Methods For Screen-detected Lung Nodulesmentioning
confidence: 99%
“…However, in addition to radiation exposure, it could not access real-time monitoring [13]. Besides, previous studies reported that the rate of post-procedure complications was high, including pneumothorax, hemorrhage and vasovagal reaction, which lengthened the period of hospitalization [14]. On the other hand, US-guided percutaneous needle biopsy for PPLs was more advantageous than CT-guided procedure, such as radiation-free, convenient and cost-effective, real-time and dynamic [15][16][17].…”
Section: Introductionmentioning
confidence: 99%